Relación entre la transferencia del canon petrolero y la calidad del gasto público en la región Loreto periodo 2007 – 2023 - Soria Chapiama, Emerson (2025)
This research analyzes the relationship between oil canon transfers and the quality of public spending in the Loreto region during the 2007–2023 period. Using a quantitative correlational approach, annual and quarterly data were employed to evaluate key variables such as the level of public investment, budget execution, and the Human Development Index (HDI). The results show a moderate positive correlation between canon transfers and the quality of public spending, indicating that increased resource flows drive public investment, although their impact on human development is limited. Significant fluctuations in the execution of the canon were also identified, reflecting challenges in resource planning and management. These findings align with previous studies highlighting the importance of administrative efficiency and strategic alignment to maximize the canon’s impact on regional development. The study concludes that, while the oil canon is a crucial source of funding, its transformative potential depends on institutional capacity to manage resources effectively. The research provides specific recommendations and proposals to optimize canon management, ensuring a positive and sustainable impact on the welfare of Loreto's population.